2012
DOI: 10.1371/journal.pone.0036823
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Response of Human Plasmacytoid Dendritic Cells to Poxvirus Infection Is Subverted by Vaccinia E3 via Its Z-DNA/RNA Binding Domain

Abstract: Plasmacytoid dendritic cells (pDCs) play important roles in antiviral innate immunity by producing type I interferon (IFN). In this study, we assess the immune responses of primary human pDCs to two poxviruses, vaccinia and myxoma virus. Vaccinia, an orthopoxvirus, was used for immunization against smallpox, a contagious human disease with high mortality. Myxoma virus, a Leporipoxvirus, causes lethal disease in rabbits, but is non-pathogenic in humans. We report that myxoma virus infection of human pDCs induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 67 publications
0
51
0
Order By: Relevance
“…In this study, we further explored the role of the E3L NTD and found that the ZBD, but not its nucleic acid-binding function, is important for PKR inhibition. It is noteworthy that the E3L ZBD, but not its Z-DNA binding activity, is likewise required to block the induction of the innate immune response and cytokine production in poxvirus-infected plasmacytoid dendritic cells (Dai et al 2011;Cao et al 2012). In contrast, the Z-DNA binding activity of E3L was previously shown to be critical for viral pathogenicity (Kim et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we further explored the role of the E3L NTD and found that the ZBD, but not its nucleic acid-binding function, is important for PKR inhibition. It is noteworthy that the E3L ZBD, but not its Z-DNA binding activity, is likewise required to block the induction of the innate immune response and cytokine production in poxvirus-infected plasmacytoid dendritic cells (Dai et al 2011;Cao et al 2012). In contrast, the Z-DNA binding activity of E3L was previously shown to be critical for viral pathogenicity (Kim et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, substitution of alanine in place of vaccinia E3L residues Y48 and P63 markedly reduced viral lethality following intracranial inoculation in mice (Kim et al 2003). In contrast to these studies revealing the importance of the E3L Z-DNA binding activity, the ability of E3L to antagonize the innate immune response in plasmacytoid dendritic cells is dependent on the ZBD, but not its Z-DNA binding activity (Dai et al 2011;Cao et al 2012). Taken together, these data reveal important roles for the E3L ZBDand its Z-DNA binding activity; however, the contribution of Z-DNA binding to E3L inhibition of PKR is not known.…”
Section: Introductionmentioning
confidence: 89%
“…2). Poxvirus infection is detected by TLR7 [47], TLR8 [48] and TLR9 [49,50] in endosomes of conventional and plasmacytoid dendritic cells (cDCs and pDCs). Survival of mice after a lethal ECTV infection was critically reliant on TLR9, while MVA infection protected mice from ECTV in a manner dependent on TLR9 [49].…”
Section: Tlrs Link Poxviral Detection To Nfkb Activationmentioning
confidence: 99%
“…Survival of mice after a lethal ECTV infection was critically reliant on TLR9, while MVA infection protected mice from ECTV in a manner dependent on TLR9 [49]. Recognition of poxvirus by TLR7 was proposed to involve detection of viral RNA transcripts [47], while surprisingly, TLR8-dependent responses were suggested to be mediated by recognition of poly(A)/T-rich poxviral DNA sequences [48]. Interestingly, although TLR3 and TLR9 are not normally expressed in skin [51,52], MCV-infected skin lesions exhibited increased expression of TLR3 and TLR9 in infected tissues, suggesting that these TLRs may be involved in the local host response to MCV in infected keratinocytes [52,53].…”
Section: Tlrs Link Poxviral Detection To Nfkb Activationmentioning
confidence: 99%
See 1 more Smart Citation